Just and Civilized Humanity - Khatri, Man Bahadur (IJRDO-Journal of Applied Science, 2015)
The UK is an advanced country in education. The oldest universities like; Cambridge,Oxford, Glasgow and Durham have been also shedding a type of impression even in presentsituation. In the field of English Language Teaching (ELT) also it has been investing a lot ofmoney every year. As a developed country, its rate of education, employment and investment ineducation is very high. Thousands of students go to the UK for higher studies and earn valuablecertificates each year. But, because of open access in higher education institutions since 1990s,a number of counterfeit higher education institutions were opened till 2010/12 and collectedmoney from the abroad students. It degraded the life of students as well as the prestige of theUnited Kingdom. More than a systematic development in education, it brought a type ofpollution in higher education so the government of UK started making amendments in highereducation policies and foreign students since 2010. So, in this study, along with lots ofappreciations, I have made some comments which would be useful for both the foreign studentsand the government of the United Kingdom in case of education.